Short sleep duration in adults with congenital heart disease is associated with epicardial adipose tissue accumulation - Stapel, Britta; Winter, Lotta; Heitland, Ivo; Halling, Tim; Akkermann, Steffen; Muke, Jochen; Löffler, Friederike; Bauersachs, Johann; Westhoff-Bleck, Mechthild; Kahl, Kai G. (Frontiers in Psychiatry, 2025)
Short sleep duration has been linked to an increased risk of cardiometabolic disorders and adverse outcomes, including hospitalization and mortality, in patients with cardiovascular disease (CVD). We assessed the association between sleep duration and cardiovascular parameters in adults with congenital heart disease (ACHD). Data were derived from the ongoing PSYConHEART study on morbidity and mortality factors in ACHD. Sleep duration, sociodemographic variables, and symptoms of anxiety and depression were measured using self-report questionnaires. Epicardial adipose tissue (EAT) was measured by echocardiography, and clinical parameters regarding the underlying heart condition, including serum levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP), were assessed. Patients with a score < 3 on the Hospital Anxiety and Depression Scale depression subscale were included (N = 194). Short sleep duration (≤ 6 h/night) was present in 48 patients (25%). Two-way multivariate analysis with sleep duration (≤ 6 h/night vs. > 6 h/night) and age (≥ 35 vs. < 35 years) as independent variables, corrected for BMI, sex, and NYHA class, revealed a significant effect of sleep duration and age on prognostic CVD markers, namely EAT and NT-proBNP. Sleep duration was associated with CVD markers in older patients only. Sleep duration was associated with CVD markers only in older patients. In particular, EAT, which has prognostic value in cardiac diseases, was negatively impacted by short sleep duration. Sleep problems/disorders are amenable to psychological and pharmacological interventions. Therefore, assessment of sleep problems/disorders may be recommended as part of the multimodal treatment of ACHD patients.